2016
DOI: 10.1097/md.0000000000004935
|View full text |Cite
|
Sign up to set email alerts
|

Attention during functional tasks is associated with motor performance in children with developmental coordination disorder

Abstract: This cross-sectional and exploratory study aimed to compare motor performance and electroencephalographic (EEG) attention levels in children with developmental coordination disorder (DCD) and those with typical development, and determine the relationship between motor performance and the real-time EEG attention level in children with DCD.Eighty-six children with DCD [DCD: n = 57; DCD and attention deficit hyperactivity disorder (ADHD): n = 29] and 99 children with typical development were recruited. Their moto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…Therefore, we postulate that 3 months of TKD training may not be long enough to elicit a training effect in EHC reaction time. Another plausible reason was that our reaction time test (a finger-pointing task) results could be confounded by the attention level of the participants with DCD who are known to be inattentive to motor tasks 22 . Therefore, further study may monitor the attention level of the participants concurrently during the EHC test 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we postulate that 3 months of TKD training may not be long enough to elicit a training effect in EHC reaction time. Another plausible reason was that our reaction time test (a finger-pointing task) results could be confounded by the attention level of the participants with DCD who are known to be inattentive to motor tasks 22 . Therefore, further study may monitor the attention level of the participants concurrently during the EHC test 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Wilmut et al (26) found that the slow response to exogenous attention distribution among children with DCD was only observed in tasks involving the integration of visual actions. To further clarify the relationship between attention and movement performance among children with DCD, more recent studies have used electroencephalogram recordings taken from the foreheads of participants and subsequently converting them into indicators of attentional levels, with the results indicating a correlation between attention level and movement performance among children with DCD (27).…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first study to use a mobile single-channel EEG device to monitor TMo surgeries; for this reason, there is no comparative method. It should be viewed as an exploratory study with highly interesting points that may direct the development of a new device for identifying biological markers to explore surgical stress in oral surgery; NBSKeeg, used in this research, shows fair validity and reliability, and it has been employed by several clinical studies [ 10 11 12 13 23 24 25 26 ]. Clinical modifications of the initial protocol, such as expanding the EEG monitoring period to cover the full surgery and clinically time-controlling the events of the trans-surgical development, could also be an interesting approach.…”
Section: Discussionmentioning
confidence: 99%